The occupation-centered intervention assessment a reflection tool for occupation-centered practice - Jewell, Vanessa D.; Pickens, Noralyn D.; Wienkes, Taylor L. (North Bethesda American Occupational Therapy Association, 2022)
The Occupation-Centered Intervention Assessment (OCIA) was developed to provide occupational therapy students, educators, and practitioners with a tool to guide reflective practice to improve development and implementation of occupation-centered interventions. This OCIA instruction manual aids students, educators, and practitioners in understanding how to assess their current practice or teaching strategies using an occupation-centered approach, use the OCIA to score their own interventions or teaching strategies, and identify strategies to immediately implement occupation-based and occupation-focused interventions and teaching strategies into current clinical practice and classroom instruction"--